2023
DOI: 10.21608/ejz.2023.231135.1103
|View full text |Cite
|
Sign up to set email alerts
|

Potential Ameliorative Effect of Propolis Against the Developmental Toxicity Induced by Oxaliplatin in Albino Rats Prior and During Pregnancy

Zeinab Kamal,
Ebnalwaled Ahmed,
Dorreia Zaghloul
et al.

Abstract: Oxaliplatin (OXA), belongs to the class of platinum-based antitumor drugs. Among the standard chemotherapeutic agents, OXA succeeded in the treatment of different tumors. However, using of OXA prior or during pregnancy constitutes health challenge to mothers and their offspring owing to cumulative outcome. Propolis (PRO) is a resinous product collected by the bee "Apis mellifera" from plants to cement the beehives, and has a protective efficiency against many medication-toxicity. The present study aimed to app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Additionally, the biological role of propolis is frequently through presence of flavonoids, which are known as various influences on health [39] . The GC-MS analysis of the used propolis extract in the current study identified the major classes of the bioactive compounds in propolis perhaps are responsible for favorable health activity as hexadecanoic acid, oleic acid, and pentadecanoic acid [18] . Zulhendri et al [40] reported that the bioactive compounds in propolis possess a wide range of biological activities including hepatoprotective, antitumor, antioxidative, and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Additionally, the biological role of propolis is frequently through presence of flavonoids, which are known as various influences on health [39] . The GC-MS analysis of the used propolis extract in the current study identified the major classes of the bioactive compounds in propolis perhaps are responsible for favorable health activity as hexadecanoic acid, oleic acid, and pentadecanoic acid [18] . Zulhendri et al [40] reported that the bioactive compounds in propolis possess a wide range of biological activities including hepatoprotective, antitumor, antioxidative, and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 83%
“…Crude propolis was purchased from Elhassan Bee House in Qena City, Egypt. Aqueous extract of propolis was prepared as described previously [18,20] .…”
Section: Chemicals and Propolis Extractionmentioning
confidence: 99%
See 2 more Smart Citations